Aorto-bi-Femoral Bypass for Juxtarenal Aortic Occlusion in a Patient with Multiple Co-Morbidities: Report of a Challenging Case - Bashar, AHM; Samad, S; Hossain, ASMI; Sabah, MN; Hasan, K; Alauddin, M (Cardiovascular Journal, 2014)
Aorto-bi-femoral bypass for aorto-iliac occlusive disease is a fairly common procedure in vascular surgical practice. The procedure, despite its extensive nature, is generally well tolerated particularly by those having an infrarenal type of aortic occlusion. Patients having a juxtarenal aortic occlusion require a considerably more expeditious surgery necessitating maneuvers to protect the renal arteries. Surgical risk increases significantly in those having multiple co-morbid conditions. We report here a successful case of aorto-bi-femoral bypass for juxtarenal aortic occlusion in a patient having multiple co-morbid conditions like ischemic heart disease, occluded right renal artery with chronic kidney disease, severe malnutrition, hypertension and chronic obstructive pulmonary disease. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18363 Cardiovasc. j. 2014; 6(2): 170-174